2006
DOI: 10.1080/15363830500538425
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Size Effects on Carbon Nanotubes' Mechanical Properties by Using Different Potential Functions

Abstract: We use molecular mechanics calculations to study size effects on mechanical properties of carbon nanotubes. Both single-walled nanotubes (SWNTs) and multiwalled nanotubes (MWNTs) are considered. The size-dependent Young's modulus decreases with the increasing tube diameter for a reactive empirical bond order (REBO) potential function. However, we observe a contrary trend if we use other potential functions such as the modified Morse potential function and the universal force field (UFF). Such confliction is on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 20 publications
4
24
0
Order By: Relevance
“…For set 2 MWCNTs, Young's modulus as well as buckling strain is more sensitive to the outer diameter than the wall number. Again the dependence of Young's modulus on wall number for the set 2 MWCNTs is also confirmed by other researchers 10,11,18,20 36 using a tight-binding ͑TB͒ method͔.…”
Section: A Young's Modulussupporting
confidence: 71%
See 2 more Smart Citations
“…For set 2 MWCNTs, Young's modulus as well as buckling strain is more sensitive to the outer diameter than the wall number. Again the dependence of Young's modulus on wall number for the set 2 MWCNTs is also confirmed by other researchers 10,11,18,20 36 using a tight-binding ͑TB͒ method͔.…”
Section: A Young's Modulussupporting
confidence: 71%
“…For a given inner diameter, the outer diameter of MWCNTs is increased with respect to the wall number. It is concluded by numerous studies 7,11,15,18,20,35 that Young's modulus is inversely dependent on the outer diameter of SWCNT, i.e., a larger outer diameter leads to a lower Young's modulus. For example, Young's modulus of the ͑20,20͒ SWCNT as shown in Table III is 0.9937 TPa, which is smaller than the 1.2853 TPa of the ͑5,5͒ SWCNT with a smaller diameter in Table IV.…”
Section: A Young's Modulusmentioning
confidence: 99%
See 1 more Smart Citation
“…However, classical continuum mechanics is a scale-free theory and cannot account for effects arising from small size. Experimental [5][6][7][8] and atomistic simulations 9,10 have evidenced a significant "size-effect" in mechanical and physical properties when the dimensions of the structures become "small." Size effects are related to atoms and molecules that constitute the materials.…”
Section: Introductionmentioning
confidence: 99%
“…Their basic hexagon units are perpendicular to each other; therefore, the size-dependent Young's modulus should be different. It was reported that the Young's modulus increases with the decreases of the tube radius [36,37]; but opposite trends were also reported [32,33]. …”
Section: 2mentioning
confidence: 86%